TANTANGAN DAN STRATEGI GURU SEKOLAH DASAR DALAM MENERAPKAN PENDEKATAN DEEP LEARNING: SYSTEMATIC LITERATURE REVIEW - Alma Sinta Cahyaningrum; Bidayatul Khusna; Aris Nurkhamidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The deep learning approach plays a strategic role in enhancing the quality of learning in primary schools, particularly by fostering students' conceptual understanding and critical thinking skills. This study aims to identify the challenges involved and formulate strategies for implementing deep learning in primary school settings. To achieve this, the research employs a Systematic Literature Review (SLR) approach, involving a systematic analysis of scholarly articles published between 2022 and 2026. The findings indicate that key obstacles include teachers' limited understanding of deep learning concepts, varying levels of teacher readiness to apply this approach, and a lack of adequate supporting facilities and infrastructure. Meanwhile, identified implementation strategies include providing professional training for educators, fostering collaboration between teachers and stakeholders, optimizing the use of digital technology, and adopting student-centered learning practices. Ultimately, the successful implementation of deep learning depends heavily on teacher competence, the adequacy of facilities and infrastructure, and the support provided by school authorities and policymakers.